Biological Aspect of Betta raja of Wild Type at Bandar Tinggi Village - Helentina Mariance Manullang; Khairul Khairul (International Journal on Advanced Science, Education, and Religion, 2020)
Betta raja is endemic wild Betta fish whose habitat is found in Sumatera Island. One of the habitat found in Desa Bandar Tinggi, Kecamatan Bilah Hulu, Kabupaten Labuhanbatu. Population B. raja is increasingly diminished due to illegal logging and land conversion. The purpose of this research is to know the biological aspects of Lakepe fish (B. raja) in their natural habitat in Bandar Tinggi Village, Labuhan Batu Regency. Monitoring of biological aspects of B. raja in its original habitat needs to be. Considering B. raja as the biological wealth of endemic fish species that needs to be preserved. Methodology: The study uses exploratory methods with the determination of purposive sampling observation stations. Samples of fish captured using a fishing rod. The results of the study showed the value of b < 3, then the pattern of fish growth is negative allometric, the population density of average fish is 0.33 – 0.40 Ind/m², and and sex ratio of females and males (1:1 ) Keywords: Betta raja, Biological Aspect, Desa Bandar Tinggi